Cariologia e filogenia molecular em Trinomys e Proechimys (Echimyidae, Rodentia) - Machado, Marianna Xavier (2017)
The family Echimyidae Gray, 1825 is the most diverse of the neotropical rodents, being a good example of rapid ecological and phenotypic diversification throughout the evolutionary history. The taxonomic history is confused, with several generic names proposed and others abandoned. However, recent works involving morphometric and phylogenetic studies have clarified the relationships between family members and also the karyotypes has been helpful to the diagnosis of the species. Within the Echimyidae family, Proechimysis the most complex genus. For about a century, it was divided into two subgenres: Trinomysrestricted to the Atlantic Forest and Proechimysdistributed from Honduras to the south of Paraguay. Only in 1996, based on studies with mitochondrial DNA sequences, Trinomyswas elevated to gender. Trinomys, in turn, is treated as one of the most complex genera in eastern Brazil. The karyotype data present in the literature have revealed that the genera Proechimysand Trinomysharbor a greater diversity of taxa than is recognized, revealing the need for an investigation using tools with good discriminatory power. The present work aimed to compile, reinterpret and determine the karyotype diversity of Trinomysand Proechimys, associating karyotypes to the geographic distribution and, through phylogenies generated by DNA sequences of nuclear and mitochondrial genes, associates clades and karyotypes. The first chapter addresses a study of molecular phylogeny and cytotaxonomy of Trinomys, in which karyotypes and sequences of 62 new specimens were added tothose available in the literature to recover molecular phylogenies using the citB and vWF genes, in order to evaluate if the karyotype is a good marker for the diagnosis of taxa. The karyotypes of T. paratusand T. setosus denigratuswere described for the first time. The phylogenetic reconstruction of the concatenated data recovered ten evolutionary lineages with high support, each associated to a Trinomysspecies. The karyotypes associated with each clade were distinct from each other, with no sharing ofkaryotype forms among species. Identical karyotypes, together with the absence of monophyletic and low values of genetic divergence, do not support the division of T. gratiosusinto two subspecies (T. g. gratiosus and T. g. bonafidei), as well as T. albispinus(T. a. minorand T. a. albispinus). However, we confirmed the three subspecies for T. setosus: T. s. setosus, T. s. elegansand T. s. denigratus, recovering the status of a valid subspeciesfor denigratus. Thus, the results obtained reinforce the importance of karyotype data in the characterization of Trinomysspecies. The second chapter investigates the karyotype variation in a new species of Proechimysfrom the 11goeldiigroup, and analyzed the karyotypes and mitochondrial DNA sequences of two specimens, one with 2n=15 and one with 2n=17, and reconstructed the molecular phylogeny with several representatives of Proechimys, aiming to find evidences to identify the mechanism of karyotype evolution and the phylogenetic position of these specimens in the genus Proechimys. It was verified that the specimens with 2n=15 and 2n=17 recovered a monophyletic clade within the goeldii speciesgroup, with low intraclade divergence (2,26%), distinct from P. goeldiiand P. longicaudatus, with interclade divergence of 12,78% and 12,06%, respectively. Contrary to what has been suggested in the literature, in which the karyotype variation is due to a multiple sex determination system of type XX: XY1Y2, with 2n = 17 exclusive to males, our data associated with reinterpretation and analysis of all karyotypic data available in the literature, confirmed that this is an autosomal rearrangement, present in both sexes, and that the karyotype with 2n=17 would be resulted of a fusion/fission process of pairs 1 and 7 (from a putative2n=18, with all the acrocentric chromosomes) and the karyotype with 2n=16 would be the homomorphic form with rearrangement between 1 and 7. The karyotypes with 2n=15 and 2n=14 are heteromorphic and homomorphic forms, respectively, of the rearrangement between the pairs 2 and 3. The genetic divergence within this clade is compatible with others for intraspecific divergence, involving individuals with 2n=15 and 2n=17, and equivalent to a new species other than those valid for Proechimys. Our data reinforce the association of this táxon to the goeldiispecies group and still deserves a formal species description. The third chapter evaluates the use of the karyotype as a specific marker for the genus Proechimys, with cytogenetic analysis of 43 new specimens, which were incorporated into those available in the literature, allowing the compilation of 1125karyotype specimens of Proechimys, with a collection of 39karyotypes The molecular phylogeny of the vWF and citB genes recovered thirteen evolutionary lineages,two of which have not yet been described for species of the genus. The karyotypes, when available, were associated with their respective DNA sequence in phylogeny in order to verify if the karyotype is associated with the monophyletic clades. We showed the formation of subgroups in some taxa, with high support. In P. cuvieri, clade A (2n=28/FN=46) presented 8,86% of genetic divergence between clade B (2n=28/FN=48) and 10,36% in relation to clade C, with no associated karyotype), whereas clade B differed by3% from clade C, suggesting that A (P. cuvieri, 2n=28/FN=46) is a taxonomic unit other than B (2n =28/ FN=48 ) and C, which should represent a species still to be described. In P. longicaudatus, two clades diverged from each other by 10.75%, and the cladeassociated with the 2n=28/FN=50 karyotype was 12identified as P. longicaudatus, while that associated with 2n=28/FN=48-50 should belong to a taxonomic unit not yet described. In P. roberti, the karyotype 2n=30/FN=56 in clade A showed low divergence in relation to clades B (3,31%) and C (2,93%), but high divergence in relation to clade D (6,94%), associated with the karyotype 2n=30/FN=56, but the morphology of the last pair is distinct from the cytotype in A. Our analysis suggests that the clade D with disjunct distribution, high divergence and distinct karyotype should correspond to a distinct taxonomic unit. Proechimys guyannensispresented as the most complex species due to the great karyotypic diversity associated to this species. The phylogeny showed three subgroups: A, B and C, with relatively low divergence, clade B diverged in 2.45% of clade A, clade C in 5,22% of B and clade C in 5,49% of A. Although low diversity, monophyly, disjunct geographical location and distinct karyotypes allowed to associate the karyotypes of P. guyannensis: 2n=40/FN=50-52, for Amapá, French Guiana and Venezuela (clade B); 2n=46/FN =50 to the east of Amazonas, Roraima and Pará (clade A) and 2n=38/52 to clade C to the extreme northwest of Amazonas. The latter presents remarkablekaryotypic variations and the greater divergence when compared to the other clades, could represents an effective barrier to the intercrossing between these individuals and those of the other clades. Due to the absence of phylogenetic resolution of the basal in P. guyannensis, low number of specimens analyzed under molecular and karyotype approaches, additional efforts are necessary, since this taxon can represent a set of species. Representatives of P. steereiwere not karyotyped in this study but the review in literature allowed to associate each karyotype with their respective sequence. The cytotypes 2n=24/FN=40-42, with variation of the FN due to pericentric inversion events in pair 3 are recognized. Our analysis indicated no structuring in the distribution of the karyotypesandthe variation of the FN within P. steerei(FN=40-42) as a chromosomal polymorphism, with FN=41 being the intermediate form between the two homomorphic